Technological Improvement of the Panela Packaging Process Using a Heat Recovery and Heat Sealing System - Gómez Meneses, Fabio Camilo; Moran Perafán , Richard; Ibarra , Álvaro (I+ T+ C- Research, Technology and Science, 2023)
In the context of panela processing and its technological improvement, this article addresses the implementation of technological enhancements in the packaging process by incorporating a heat recovery system and developing a heat sealing tunnel. The study aims not only to enhance the efficiency of the packaging process but also to reduce energy consumption and improve the quality of the end product. Regarding the methods, a detailed analysis of heat loss during panela production was conducted, and a heat recovery system was designed to harness this energy. Furthermore, an energy analysis of the panela production plant was initially carried out to determine the appropriate point for implementing the recovery system. Based on this information, an innovative heat sealing tunnel was developed to ensure the packaging quality of the product, working from the mechatronic design perspective.In terms of results, the energy efficiency of the plant was identified, along with a notable improvement in energy efficiency in heat recovery, directing it towards the heat sealing system. This, in turn, had a positive influence on the quality of the packaged panela, thanks to the proper sealing provided by the new heat sealing tunnel. In conclusion, this study demonstrates that the combination of heat recovery and heat sealing technologies has a significant impact on the efficiency and quality of the panela packaging process in terms of sustainability and process improvement.